Gambaran Pendekatan Model Copa pada Perawat Pelaksana di Rumah Sakit Abdul Manap Kota Jambi - Dwi Yunita Rahmadhani (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The safety of hospital patients is the hospital system to make patient care safer. Safe from the possibility of the risk of Patient Safety Incidents (IKP). One that can override the Model COPA patient safety is requesting more competent, safe practices, verified by examination performance. This study used a descriptive correlation design with cross sectional approach. The goal is to obtain COPA analysis model approach and the determinant factors of nurses with patient safety. The population is all nurses in inpatient hospital Abdul Manap city of Jambi. The number of samples in this study were 50 nurses using total sampling technique. In the bivariate analysis, obtained variables skills assessment and intervention, communication, critical thinking, human caring and relations of social, management, leadership, teaching and integration of science, gender, type of education, length of work, married status, employment status, accreditation campus, GPA, there is a significant association with patient safety with p-value <0.005. Meanwhile, to test each dependent variable and independent variables used chi square test. Multivariate analysis using logistic regression. For that to hospitals in hiring the necessary consideration in terms of the skill factor, for workforce training nurses for patient safety and hospital complements the SPO and equipment less.